"Resources‐Demands Ratio": Translating the JD‐R‐Model for company stakeholders. Issue 1 (27th November 2019) - Jenny, Gregor J.; Bauer, Georg F.; Füllemann, Désirée; Broetje, Sylvia; Brauchli, Rebecca
Abstract: Objectives: Practitioners and organizational leaders are calling for practical ways to explain and monitor factors that affect workplace health and productivity. This article builds on the well‐established Job Demands‐Resources (JD‐R) model and proposes an empirically tested ratio that aggregates indicators of job resources and demands. In this study, we calculate a ratio of generalizable job resources and demands derived from the JD‐R model and then translate the ratio into the language of company stakeholders. Methods: We calculated a ratio based on measures applied in a large stress management intervention study (n = 2983) and report the findings from cross‐sectional analysis with health and productivity outcomes from same‐source and separate‐source data. Results: Findings showed a strong and unambiguous increase in health and productivity measures with each step of increase in the ratio. Loss in explained variance due to aggregation of two factors into a single ratio is small for measures which are known to be predicted by both factors simultaneously. Conclusions: A translation and visualization of the ratio that is accessible to practitioners and organizational leaders is presented and its use in companies discussed.